Spherical Helices for Resonant Wireless Power Transfer - Maja Škiljo; Zoran Blažević (International Journal of Antennas and Propagation)
The capabilities of electrically small spherical helical antennas for wireless power transmission at small and moderate distances are analyzed. Influence of design on antenna radiation resistance, efficiency, and mode ratio is examined. These are the factors that, according to the theoretical considerations depicted herein, govern the maximum transfer performances. Various designs and configurations are considered for the purpose, with accent on small-size receivers suitable for implementation in powering common-sized gadgets. It is shown that spherical helix design is easily manipulated to achieve a reduced antenna size. Good radiation characteristics and impedance match are maintained by multiple-arm folded antenna design and by adjusting the separation between the arms.